2004
DOI: 10.1007/s00244-004-3138-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Tissue Distribution of Metals in Birds in Sweden Using ICP-MS and Laser Ablation ICP-MS

Abstract: Cadmium, copper, lead, palladium, platinum, rhodium, and zinc profiles were investigated along feather shafts of raptor and other bird species by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The distribution of external versus internal metal contamination of feathers was investigated. The species examined were peregrine falcon (Falco peregrinus), sparrowhawk ( Accipiter nisus), willow grouse (Lagopus lagopus), and house sparrow (Passer domesticus) in Sweden. For habitat comparisons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 41 publications
4
39
1
Order By: Relevance
“…High concentrations of Cu were observed in feathers, which may be attributed to the participation of this element in the keratinization process. However, concentrations were even higher in the liver, which is corroborated by the results obtained in study carried out in Sweden [10], who demonstrated that Cu is heavily accumulated in the liver and kidneys.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…High concentrations of Cu were observed in feathers, which may be attributed to the participation of this element in the keratinization process. However, concentrations were even higher in the liver, which is corroborated by the results obtained in study carried out in Sweden [10], who demonstrated that Cu is heavily accumulated in the liver and kidneys.…”
Section: Discussionsupporting
confidence: 75%
“…The deposition of compounds in external parts of the feathers can occur through chemical products, the air, or the uropygial gland of birds [15]. According to research, 50% to 98% of the concentrations of Pb detected in organisms can originate from external contamination, although it may also occur due to contaminated feed [10]. It should be considered that the origin of the birds in this study contributes significantly to the results obtained for some metals since the airport region, as well as the surrounding area, is rich in fossil fuels.…”
Section: Discussionmentioning
confidence: 99%
“…These results can serve as a baseline for comparison with future studies of contaminant exposure in Bald Eagles across Iowa as well in other locations. The contaminant levels we observed in excrement samples collected from Bald Eagles were within the range of concentrations reported in other avian species (Ek et al 2004, Morrissey et al 2005, Tiller et al 2005, Berglund et al 2010, Costa et al 2013, Martinez-Haro et al 2013). The majority of these studies, it should be noted, focused on passerines and waterfowl.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the median Cd concentrations were about 0.15 µg/g. Nickel content in birds can reach 5 µg/g (Eisler 1981). In our study, the median value for Ni in feather was about 2 µg/g -2.5 µg/g (Figure 1).…”
Section: Elemental Characterization Of Feather Samples By Bulk Analysismentioning
confidence: 99%
“…In our study, the median value for Ni in feather was about 2 µg/g -2.5 µg/g (Figure 1). Nickel concentrations in avian tissues in excess of 10 µg/g dry weight (DW) kidney or 3 µg/g DW liver are sometimes associated with adverse effects (Eisler 1981). Excess Ni is reported to affect feather molting (Malik and Zeb 2009).…”
Section: Elemental Characterization Of Feather Samples By Bulk Analysismentioning
confidence: 99%